Policy Spillovers in a Regional Target-Setting Regime - J. Kim Swales; David Learmonth (European Regional Science Association (ERSA), 2005)
The specific concern in this paper is the co-ordination difficulties within a target-setting regime where there are negative policy spillovers across regions and where these spillovers are not common knowledge amongst the government and the delegated agencies. We analyse this policy problem in a principal-agent framework, using a very simple model. In this model it is possible for both the government (the principal) and the regional agencies (the agents) to be either informed or uninformed about the nature of the inter-regional spillovers. Further, informed development agencies can either act non-cooperatively or collusively in attempting to meet the policy targets. We demonstrate that: ·where one policy objective has negative spillovers, there will be a switch in expenditure towards that policy that has the externality, ·the expenditure switch will be largest when the spillover is greatest ·where the agency is informed, the expenditure switch is reduced, ·if the number of informed agencies is increased, the extent of expenditure switching is increased unless the agencies collude, ·that such expenditure switching is arbitrary and likely to be welfare reducing ·adjustments to the targets by an uninformed government may make matters worse. The analysis is primarily done diagrammatically.
Keywords: 330